A africação na interlíngua português-inglês na região de colonização italiana do nordeste do Rio Grande do Sul - Dani, Luana Tiburi (My University, 2014)
The dependent variable of this study is the spurious affrication (or palatalization) of alveolar stops /t/ and /d/ in Brazilian Portuguese-English interlanguage of learners of the same speech community in Caxias do Sul, town which belongs to the Italian Colonization Region in Northeastern Rio Grande do Sul. In Brazilian Portuguese, alveolar stops are subject to allophonic processes and serve as a dialect marker. Considering L1 transfer, it is expected that the production of English final alveolar stops is problematic, as it is inferred by Bettoni Techio (2005). Through Interlanguage Analysis, we investigated the L2 phonology of sixteen beginning learners of English as a Foreign Language. There was rule application in 5.3% of contexts obtained. The independent variables of the study were: L1 transfer, other(s) L2 transfer, variability due to: a) linguistic environment, b) gender, c) ancestry and d) linguistic attitude. Out of the controlled variables, variability due to the linguistic environment (composed of following context, voicing and tone) was considered significant by statistical tests carried out for this study. In the community of speech and practice investigation, spurious affrication (or palatalization) of alveolar stops in Brazilian Portuguese-English interlanguage is conditioned favorably by the factors: a) target sound /t/ and /d/ followed by a vowel, b) voiceless target sound /t/ and c) target sound in stressed syllable.
A variável dependente deste estudo é a africação (ou palatalização) espúria das oclusivas alveolares /t/ e /d/ na interlíngua português-inglês de aprendizes de uma mesma comunidade de fala em Caxias do Sul, município pertencente à Região de Colonização Italiana do Nordeste do Rio Grande do Sul. No português brasileiro, as consoantes alveolares são suscetíveis a processos alofônicos e servem como um marcador dialetal, portanto sua produção em inglês pode tornar-se problemática, conforme se depreende da leitura de Bettoni Techio (2005). Por meio da Análise de Interlíngua, investigamos a L2 de 16 participantes aprendizes de língua inglesa como língua estrangeira em nível inicial de aprendizagem. Houve aplicação da regra em 5,3% dos contextos obtidos. As variáveis independentes do estudo foram: transferência da L1, transferência de outra(s) L2, variabilidade devido(a) à/ao: a) ambiente linguístico, b) gênero, c) ascendência e d) atitude linguística. Das variáveis controladas, variabilidade devido ao ambiente linguístico (composta por contexto seguinte, sonoridade, e tonicidade) foi considerada significativa pelo testes estatísticos realizados para o estudo. Na comunidade de fala investigada, a africação (ou palatalização) espúria de oclusivas alveolares na interlíngua português-inglês é condicionada favoravelmente pelos fatores: a) consoante-alvo /t/ e /d/ seguida de vogal, b) consoante-alvo desvozeada e c) consoantealvo localizada em sílaba tônica.
Keywords: Língua portuguesa; Palatalização; Língua inglesa; Sociolinguística; Aquisição da segunda língua